1996
DOI: 10.1679/aohc.59.467
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Study of Follicles in the Senescent Porcine Pituitary Gland.

Abstract: Summary. Follicles displaying a positive periodic acidSchiff reaction to a colloid substance in the anterior pituitary gland have been observed in many vertebrates, including humans. It is also known that these follicles greatly increase in number and size with age. We therefore performed histochemical analysis of these colloid follicles in the senescent porcine pituitary gland in order to clarify their nature and biological significance. Results from various histological stains suggest that the colloid contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Soji et al [1994] have shown an increase in the number of these cells in relation to age, suggesting that the expression of the S-100 protein indicates the cells` morphologic maturation stage in rats. The FSC in most pituitary glands of the studied species originated follicular structures with colloid in their lumen [Anthony and Gustafson, 1984;Ben-Jonathan et al, 1991;Kameda, 1991;Ogawa et al, 1996;Mohamed et al, 2000;Claudius et al, 2005]. In pigs and guinea pigs, a relation between the follicular colloid, the FSC and the pituitary hormone-secretory cells has been suggested [Kameda, 1991;Ogawa et al, 1997].…”
mentioning
confidence: 90%
“…Soji et al [1994] have shown an increase in the number of these cells in relation to age, suggesting that the expression of the S-100 protein indicates the cells` morphologic maturation stage in rats. The FSC in most pituitary glands of the studied species originated follicular structures with colloid in their lumen [Anthony and Gustafson, 1984;Ben-Jonathan et al, 1991;Kameda, 1991;Ogawa et al, 1996;Mohamed et al, 2000;Claudius et al, 2005]. In pigs and guinea pigs, a relation between the follicular colloid, the FSC and the pituitary hormone-secretory cells has been suggested [Kameda, 1991;Ogawa et al, 1997].…”
mentioning
confidence: 90%
“…A few studies on the mammalian pituitary also suggested a role for epithelial cells in colloid accumulation. Frequent occurrence of PRL cells and occasional LH cells in close association with stellate cells that lay next to the large colloid-containing follicles were reported, and it has been suggested that these cells in some way contribute to the formation of colloid [Ogawa et al, 1996]. Immunohistochemical study of epithelial cells in the PT of the human adult pituitary gland also elucidated that the colloid-forming follicular cells were mostly ACTH cells [Osamura and Watanabe, 1978].…”
Section: Discussionmentioning
confidence: 98%
“…Extracellular accumulations have been reported in the pituitary glands of all the vertebrate classes ranging from fish to mammals [Wingstrand, 1966;Holmes and Ball, 1974;Benjamin, 1981;Harrisson et al, 1982;Anthony and Gustafson, 1984;Ciocca et al, 1984;Dar and Sathyanesan, 1985;Kameda, 1991;Watanabe, 1991;Ogawa et al, 1996;Mohamed et al, 2000]. Accumulation of colloid in the follicular lumen and fibrous materials inside the cavities/cyst-like structures of the adenohypophysis have been reported in many vertebrates including the birds, though little information is available regarding their mode of formation, cellular types that take part in the formation of follicles or cysts, and the biological significance of these accumulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations